Bouncing Back after Pandemic: Parental Role in Raising Resilient Children - Hasanah, Riska (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
After more than two years of living in difficult circumstances, the children managed to go to school. In the new era, they need to adapt and overcome the 'losses' they gain. This review of literature provides children conditions during outbreaks and how parental roles enable children to bounce right back from adversity. More specifically, this review will examine parental factors that contribute to resilience in their children. The literature also has documented child maltreatment during changing in the learning system that happened to children.